Revision of Argentinian species of Hexacola Foerster (Hymenoptera: Figitidae: Eucoilinae) - Reche, Vanina A. (2015)
The eucoiline genus Hexacola Foerster, 1869 is present in the Afrotropical, Neotropical, Holarctic and Ethiopian regions, as well as Oceania. In this paper, three species are reported for the first time in Argentina: Hexacola hexatoma (Hartig 1841), Hexacola bifarium Quinlan, 1986 and Hexacola bonaerensis Reche, nom. nov. proposed to replace Hexacola fuscipes (Kieffer 1908) by homonymy with Hexacola fuscipes (Kieffer 1907). Their redescriptions are provided. Species from Argentina are parasitoids of Ephydridae and Chloropidae (Diptera). New distribution data, new host records and a key for Argentinian species are provided. Photographs of diagnostic characters and georeference of locality of collections are included. The material examined is deposited in the collection of the División Entomología, Museo de La Plata (Argentina).